Evaluation of mercury in skin lightening creams commonly used in Trinidad and Tobago and their associated health risk - Mohammed, Terry; Rambocas, Nadira; Basdeo, Sanjeev; Kissoon, Yasphal (The European Research Journal, 2024)
Objectives: This study investigated the presence of mercury in commonly used over the counter skin-lightening creams available in Trinidad and Tobago. The objective of this study was to evaluate if skin-lightening creams commonly used in Trinidad and Tobago contained Mercury, and establish the health risks presented by these products. Methods: Nineteen skin-lightening creams were analysed using Cold Capor Atomic Absorption Spectrophotometry (CV-AAS). Margin of Safety (MoS) and Hazard Quotient (HQ) calculations were used to assess risk to users. Results: Of the nineteen creams assessed, sixteen contained high concentrations of mercury (0.294-14414.5 µg/g), only three creams had no mercury detected. 9 of the 19 samples contained levels of mercury that exceed the Minamata convention’s accepted limit of 1µg/g, with 3 samples exceeding 3800.000 µg/g. Risk assessments using MoS and HQ showed that 3 of the samples were unsafe for use and are considered hazardous. The study also revealed that many creams do contain mercury even if it did not constitute part of the product formulation. Conclusions: The data infers that some manufacturers do add mercury to their formulations while others are the victims of contaminated raw materials. MoS and HQ show that 21% of the samples were unsafe and 16% can be considered hazardous for human use. It is possible that with such levels of mercury in these products and the popularity of these products within the Caribbean Community and its diaspora, that there exists a significant amount of members with higher than acceptable mercury levels, with undiagnosed clinical symptoms.